Posted by deedra on Sunday, June 14, 2009 at 11:32pm.
If they are two separate terms, both have v as a factor rather than 6v.
v^3 + 6v^2 +9v = v(v^2 + 6v + 9) = v(v + 3)(v + 3)
v^2 - 6v = v(v - 6)
I hope this helps. Thanks for asking.
dividing a polynomial by a polynomial - (-6v^2 - 4 + 9v +v^3)/ (v - 4)i am just...
Math - Simplify: -1+9(5-3m) Solve 10=10-2m Solve: 4b<_-2/3 Simplify: 6v-8...
algebra - 22-5(6V-1)=-63
College algebra - Solve. V^2-6v-16=0
algebra - v^2-36 6 -v my answer (v+6)(v^2-6y+36 6v
mathematics - find the product using suitable identity 1)(5u-6v)raise to 2
Physics - A capacitor consists of two concentric spherical shells. The outer ...
math - -v+5+6v=1+5v+3 how would i get the value of v
algebra - When I multiply 6v^9*10v^7 I get 60v^16 My question is, do I add the 9...
algebra - (-6^2 + 2v + 4) - (6v^2 + 4)= Is the solution: 12v^2 + 2v?
For Further Reading